Modified molecular sieve, preparation method and application thereof
Patent Information
- Application Number
- CN202410638760.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-22
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-05-22
AI Technical Summary
然而,在轻烃催化裂化反应中,伴随着焦炭污染催化剂表面,堵塞微孔孔道,导致ZSM-5分子筛失活
[0028]本发明提供了一种改性分子筛,所述改性分子筛包括硅铝分子筛和存在于所述硅铝分子筛的孔道中的氧化钙;所述硅铝分子筛具有微孔和介孔的复合孔道结构。在本发明中,所述改性分子筛可以作为轻烃裂解中的活性成分使用,其微孔和介孔的复合孔道结构有利于油气组分进入其孔道中进行反应,可有效提高反应的转化率。同时,相较于具有单一微孔孔道的分子筛,较大的介孔结构明显降低了产物的扩散阻力,避免烯烃发生二次反应,有利于提高双烯的选择性。此外,由于氧化钙中的Ca元素能够均匀分布在分子筛的孔道结构中,降低了分子筛的酸性位点密度,使分子筛中的酸性分布更为均匀,可抑制氢转移反应,提高双烯选择性,并提高分子筛的抗结焦能力。
Smart Images

Figure CN118598148B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of catalyst preparation technology, specifically relating to a modified molecular sieve, its preparation method, and its application. Background Technology
[0002] Light olefins, such as ethylene and propylene, can serve as feedstocks for the production of chemicals such as resins, polyethylene, polypropylene, ethylene oxide, and fibers. Currently, light hydrocarbon catalytic cracking is a promising alternative to thermal cracking, offering higher energy efficiency and higher yields of propylene and ethylene at relatively lower temperatures. ZSM-5 molecular sieves have been widely used in light hydrocarbon catalytic cracking due to their high thermal stability, hydrothermal stability, resistance to deactivation, acidity and activity, cation exchange capacity, ordered pore structure, and unique framework structure. However, in light hydrocarbon catalytic cracking reactions, coke contamination of the catalyst surface and blockage of micropores leads to the deactivation of ZSM-5 molecular sieves. Furthermore, since microporous molecular sieves restrict the diffusion and transfer of reactant and product molecules within the pores, replacing microporous ZSM-5 with hierarchical ZSM-5 as the catalyst can significantly improve catalyst activity and resistance to coking. In recent years, some researchers have investigated the performance of metal-supported ZSM-5 molecular sieves in catalytic cracking reactions. The results show that metal-supported ZSM-5 molecular sieves can reduce the density of acidic sites in the molecular sieve, make the acidic distribution in the molecular sieve more uniform, inhibit hydrogen transfer reactions, improve diene selectivity, and also improve the anti-coking ability of the molecular sieve.
[0003] For example, CN117430126A discloses an iron-containing ZSM-5 molecular sieve. By using ligands to encapsulate the iron active component inside the ZSM-5 molecular sieve, an iron-encapsulated ZSM-5 molecular sieve is prepared. When used in the catalytic cracking reaction of light hydrocarbons and the catalytic cracking reaction of naphtha, it has a better yield of low-carbon olefins and can reduce the generation of non-ideal components such as coke.
[0004] CN117160528A discloses a Mn-Zn-P composite modified molecular sieve, which is prepared by mixing shape-selective cracking molecular sieve, manganese compound, zinc compound, phosphorus compound and water to form a mixed slurry. The Mn-Zn-P composite modified molecular sieve is used as a catalytic cracking catalyst for the catalytic cracking reaction of hydrocarbons (such as naphtha), and high yields of ethylene and propylene are obtained, while effectively reducing the methane yield.
[0005] As can be seen from the above invention, loading metals or introducing metals into ZSM-5 molecular sieves can not only improve the product distribution of light hydrocarbon cracking reactions, but also effectively reduce the generation of by-products such as coke and methane. Summary of the Invention
[0006] In view of this, the purpose of this invention is to provide a modified molecular sieve, its preparation method, and its application. The introduction of metallic calcium into the modified molecular sieve reduces the density of acidic sites, resulting in a more uniform acidic distribution within the sieve, which is expected to improve the conversion rate and diene selectivity of the reaction.
[0007] To achieve this objective, the present invention adopts the following technical solution:
[0008] In a first aspect, the present invention provides a modified molecular sieve, the modified molecular sieve comprising a silica-alumina molecular sieve and calcium oxide present in the silica-alumina molecular sieve;
[0009] The silica-aluminum molecular sieve has a composite pore structure of micropores and mesopores.
[0010] The ratio of the total mass of SiO2 and Al2O3 to the mass of calcium oxide in the silica-alumina molecular sieve is (40-250):1.
[0011] Preferably, the silica-alumina molecular sieve is any one or more of ZSM-5 molecular sieve, Y-type molecular sieve, ZSM-35 molecular sieve, or β molecular sieve.
[0012] Preferably, the calcium oxide is derived from calcium carbonate.
[0013] Preferably, the calcium carbonate is derived from waste eggshells.
[0014] Secondly, the present invention provides a method for preparing the above-mentioned modified molecular sieve, comprising:
[0015] The silicon source, aluminum source and calcium source are mixed under alkaline conditions, crystallized and calcined to obtain an intermediate;
[0016] The intermediate was subjected to ion exchange with an ammonium salt, and the modified molecular sieve was obtained after calcination.
[0017] Preferably, the silicon source is selected from one or more of silica sol, tetraethyl orthosilicate, or silica gel.
[0018] Preferably, the aluminum source is selected from any one or more of sodium aluminate, aluminum hydroxide, aluminum sulfate, or boehmite.
[0019] Preferably, the calcium source is selected from calcium carbonate.
[0020] Preferably, the ammonium salt is selected from any one or more of ammonium chloride, ammonium nitrate, or ammonium acetate.
[0021] Thirdly, the present invention provides a catalyst comprising a support, a binder, and an active component;
[0022] The active component is the modified molecular sieve involved in the above technical solution.
[0023] Preferably, the carrier is selected from kaolin.
[0024] Preferably, the binder is selected from any one or more of alumina sol, silica sol, acidified boehmite, water glass, or aluminum phosphate.
[0025] Preferably, the catalyst comprises, by weight, 20-40 parts of a carrier, 10-30 parts of a binder, and 30-50 parts of an active component.
[0026] Fourthly, the present invention provides an application of the modified molecular sieve or catalyst involved in the above-mentioned technical solution in the cracking of light hydrocarbons.
[0027] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0028] This invention provides a modified molecular sieve comprising a silica-alumina molecular sieve and calcium oxide present in the pores of the silica-alumina molecular sieve; the silica-alumina molecular sieve has a composite pore structure of micropores and mesopores. In this invention, the modified molecular sieve can be used as an active component in light hydrocarbon cracking. Its composite pore structure of micropores and mesopores facilitates the entry of oil and gas components into its pores for reaction, effectively improving the reaction conversion rate. Simultaneously, compared to molecular sieves with single micropores, the larger mesopore structure significantly reduces the diffusion resistance of products, preventing secondary reactions of olefins and improving diene selectivity. Furthermore, because the Ca element in calcium oxide can be uniformly distributed in the pore structure of the molecular sieve, the density of acidic sites in the molecular sieve is reduced, resulting in a more uniform acid distribution within the molecular sieve. This can inhibit hydrogen transfer reactions, improve diene selectivity, and enhance the anti-coking ability of the molecular sieve.
[0029] Tests showed that catalysts prepared using this molecular sieve as the active component in light hydrocarbon cracking, combined with a support and binder, exhibited advantages such as inhibiting hydrogen transfer reactions, reducing catalyst coking, and improving conversion rate and diene selectivity in light hydrocarbon cracking. They are particularly suitable for light hydrocarbon cracking processes that yield high diene production. Specifically, the conversion rate was above 80%, coke yield was below 6.5%, and the yields of ethylene and propylene were both above 15.5%. Calculations showed that the selectivity for ethylene was above 19.79%, and the selectivity for propylene was above 20.03%. Attached Figure Description
[0030] Figure 1 The XRD patterns of the modified molecular sieves obtained in Examples 1-7 and Comparative Example 1 are shown.
[0031] Figure 2 The images show SEM images of the modified molecular sieves obtained in Examples 1-7 and Comparative Example 1. Detailed Implementation
[0032] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0033] This invention primarily addresses the problems of catalysts in the field of light hydrocarbon cracking, such as susceptibility to hydrogen transfer and secondary reactions, and poor resistance to coking. It provides a modified molecular sieve comprising a silica-alumina molecular sieve and calcium oxide present in the pores of the silica-alumina molecular sieve. In this invention, the silica-alumina molecular sieve comprises SiO2 and Al2O3, specifically selected from any one or more of ZSM-5 molecular sieve, Y-type molecular sieve, ZSM-35 molecular sieve, or β-molecular sieve. Given the unique pore structure and pore size of ZSM-5 molecular sieve, this invention preferably uses ZSM-5 molecular sieve as the silica-alumina molecular sieve.
[0034] In this invention, the calcium oxide is preferably derived from calcium carbonate, and the calcium carbonate is preferably derived from waste eggshells. It should be noted that waste eggshells are introduced into the preparation process of the modified molecular sieve. The main component of eggshells is calcium carbonate, which can serve as a mesoporous directing agent and a source of Ca. During subsequent calcination, it decomposes into calcium oxide upon heating, thereby preparing a modified molecular sieve with a composite pore structure of mesoporous and microporous channels.
[0035] In this invention, the amount of calcium oxide introduced is crucial. If the amount introduced is too small, mesoporous channels may not be formed; conversely, if the amount introduced is too large, it will affect the application performance of the modified molecular sieve. Therefore, this invention, through screening, controls the ratio of the total mass of the silica-alumina molecular sieve to the mass of calcium oxide at (40-250):1, preferably (50-200):1, and more preferably (100-150):1.
[0036] It should be noted that the modified molecular sieve in this invention is different from conventional calcium-type molecular sieves. The difference lies in the fact that a calcium source is introduced during the preparation process of this invention. The calcium source is encapsulated inside the molecular sieve during its crystal growth and is subsequently calcined to form specific mesopores. The introduced calcium remains inside the mesopores to form calcium oxide, rather than forming Ca through ion exchange. 2+ Type of molecular sieve.
[0037] The modified molecular sieve provided by this invention can be used as an active component in light hydrocarbon cracking. Its composite pore structure of micropores and mesopores facilitates the entry of oil and gas components into its pores for reaction, effectively improving the reaction conversion rate. Simultaneously, the larger mesopore structure significantly reduces the diffusion resistance of the products, preventing secondary reactions of olefins and improving diene selectivity. Furthermore, because the Ca element in calcium oxide can be uniformly distributed in the pore structure of the molecular sieve, the density of acidic sites is reduced, resulting in a more uniform acidic distribution within the molecular sieve. This inhibits hydrogen transfer reactions, improves diene selectivity, and enhances the molecular sieve's resistance to coking.
[0038] The present invention also provides a method for preparing the above-mentioned modified molecular sieve, comprising:
[0039] The silicon source, aluminum source and calcium source are mixed under alkaline conditions, crystallized and calcined to obtain an intermediate;
[0040] The intermediate was subjected to ion exchange with an ammonium salt, and the modified molecular sieve was obtained after calcination.
[0041] According to this invention, an intermediate is obtained by mixing a silicon source, an aluminum source, and a calcium source under alkaline conditions, followed by crystallization and calcination. The silicon source is selected from any one or more of silica sol, tetraethyl orthosilicate, or silica gel; the aluminum source is selected from any one or more of sodium aluminate, aluminum hydroxide, aluminum sulfate, or boehmite; and the calcium source is selected from calcium carbonate, which is derived from waste eggshells.
[0042] In some embodiments of the present invention, the aluminum source, alkali and water are preferably mixed in a molar ratio of (1-2):(2-6):(200-300), preferably (1.5-2):(3-5):(220-280), and stirred evenly to obtain solution A. The alkali includes organic alkali and / or inorganic alkali, without particular limitation.
[0043] A silicon source and optional additives are mixed evenly in a certain proportion to obtain solution B. The additives may or may not be added, and their main function is to inhibit the growth of the b-axis of the molecular sieve. Specifically, they can be selected from any one or more of urea, ammonium fluoride, or ammonium chloride, with urea being preferred. Preferably, urea is added at a molar ratio of SiO2 to urea of (20-50):(1-3), and more preferably at a molar ratio of (30-40):(1.5-2).
[0044] Then, according to the present invention, solution B is mixed with solution A, and a certain amount of eggshell powder is added to obtain gel C. The eggshell powder is obtained by ball milling waste eggshells for 20–120 minutes to control the particle size of the eggshell powder within a suitable range, approximately 2–50 nm. Based on a total mass of 100% for both silicon and aluminum sources, the amount of eggshell powder added is 1–5 wt%, preferably 2–4 wt%.
[0045] Then, according to the present invention, gel C is crystallized at 150–180°C for 24–72 h, preferably at 160–170°C for 30–48 h. Then, preferably, the product is washed, dried, and then calcined to obtain an intermediate. The washing is preferably done with deionized water until neutral, and the drying is preferably done at 40–80°C for 5–15 h, more preferably at 50–60°C for 8–12 h. In some embodiments of the present invention, the calcination temperature is 500–600°C, preferably 520–550°C; the calcination time is 4–6 h, preferably 4.5–5.5 h.
[0046] After obtaining the intermediate, it is ion-exchanged with an ammonium salt according to the present invention, and then calcined to obtain a modified molecular sieve. The ammonium salt is selected from any one or more of ammonium chloride, ammonium nitrate, or ammonium acetate, preferably ammonium chloride. The calcination temperature is 500–600°C, preferably 520–550°C; the calcination time is 4–8 hours, preferably 4.5–6 hours. In some embodiments of the present invention, it is preferred to ion-exchange the intermediate with a 0.1 mol / L ammonium chloride solution at a solid-liquid mass ratio of 1:10.
[0047] In some specific embodiments of the present invention, the modified molecular sieves are preferably prepared by the following methods:
[0048] (1) Place waste eggshells in a ball mill and grind for 20-120 minutes to obtain eggshell powder;
[0049] (2) Stir sodium aluminate, sodium hydroxide and water evenly to obtain solution A;
[0050] (3) Mix 30% silica sol and urea evenly to obtain solution B;
[0051] (4) Pour solution B into solution A, add 1-5 wt% eggshell powder and stir at room temperature (around 25°C) to obtain gel C;
[0052] (5) Transfer gel C to a reaction vessel and crystallize it at 170°C for 24 hours;
[0053] (6) The crystallized molecular sieve was washed with deionized water until neutral, dried at 60°C for 8 hours, and calcined at 500°C for 4 hours to obtain an intermediate.
[0054] (7) Using a 0.1 mol / L ammonium chloride solution, the intermediate was subjected to ion exchange at a solid-liquid mass ratio of 1:10, and then calcined at 500℃ for 4 h to obtain the modified molecular sieve.
[0055] The above preparation method is simple, convenient, and easy to implement, which is conducive to industrial production.
[0056] The modified molecular sieve prepared above can be used as an active component in light hydrocarbon cracking. Based on this, the present invention also provides a catalyst, which includes a support, a binder, and an active component. The support is selected from kaolin, the binder is selected from any one or more of alumina sol, silica sol, acidified boehmite, water glass, or aluminum phosphate, and the active component is the modified molecular sieve described above.
[0057] In some embodiments of the present invention, the catalyst comprises, by weight, 20-40 parts of a carrier, 10-30 parts of a binder, and 30-50 parts of an active component, preferably 25-35 parts of a carrier, 15-25 parts of a binder, and 35-45 parts of an active component.
[0058] In some embodiments of the present invention, the catalyst can be prepared by the following method:
[0059] The mixture of carrier, binder and active component is ball-milled, spray-molded and then calcined.
[0060] The calcination temperature is 500–600℃, preferably 520–550℃; the calcination time is 2–8h, preferably 2–6h.
[0061] This invention also provides an application of the above-mentioned modified molecular sieve or catalyst in light hydrocarbon cracking. The catalytic cracking feedstock in the light hydrocarbon cracking is one or a mixture of C5-C8 alkanes, olefins, and aromatics.
[0062] Tests showed that catalysts prepared using this molecular sieve as the active component in light hydrocarbon cracking, combined with a support and binder, exhibited advantages such as inhibiting hydrogen transfer reactions, reducing catalyst coking, and improving conversion rate and diene selectivity in light hydrocarbon cracking. They are particularly suitable for light hydrocarbon cracking processes that yield high diene production. Specifically, the conversion rate was above 80%, coke yield was below 6.5%, and the yields of ethylene and propylene were both above 15.5%. Calculations showed that the selectivity for ethylene was above 19.79%, and the selectivity for propylene was above 20.03%.
[0063] To further illustrate the present invention, the following embodiments provide a detailed description. The experimental materials used in the following embodiments of the present invention are all commercially available products.
[0064] Comparative Example 1
[0065] (1) Add 3 mol sodium aluminate and 5 mol sodium hydroxide to 600 mol water and stir until homogeneous to obtain solution A;
[0066] (2) Mix 133 mol of 30% silica sol and 5 mol of urea evenly to obtain solution B;
[0067] (3) Pour solution B into solution A and stir at room temperature (around 25°C) to obtain gel C;
[0068] (4) Transfer gel C to a reaction vessel and crystallize it at 170°C for 24 hours;
[0069] (5) The crystallized molecular sieve was washed with deionized water until neutral, dried at 60°C for 8 hours, and calcined at 500°C for 4 hours to obtain solid a;
[0070] (6) Using a 0.1 mol / L ammonium chloride solution, solid a was subjected to ion exchange at a solid-liquid mass ratio of 1:10, and then calcined at 500℃ for 4 h to obtain solid b;
[0071] (7) Using solid b (i.e., molecular sieve) as the active component of the catalyst, add 600g of kaolin, 130g of alumina sol, 400g of molecular sieve and 130g of silica sol in sequence, mix and stir to form a slurry, ball mill the slurry and then spray it in a spray dryer.
[0072] (8) The prepared microspheres were calcined at 500℃ for 2 hours to obtain the catalyst.
[0073] Example 1
[0074] (1) Place the waste eggshells in a ball mill and grind for 20 minutes to obtain eggshell powder;
[0075] (2) Add 3 mol sodium aluminate and 5 mol sodium hydroxide to 600 mol water and stir until homogeneous to obtain solution A;
[0076] (3) Mix 133 mol of 30% silica sol and 5 mol of urea evenly to obtain solution B;
[0077] (4) Pour solution B into solution A, add 1 wt% of eggshell powder (total mass of sodium aluminate and sodium hydroxide), and stir at room temperature (around 25°C) to obtain gel C;
[0078] (5) Transfer gel C to a reaction vessel and crystallize it at 170°C for 24 hours;
[0079] (6) The crystallized molecular sieve was washed with deionized water until neutral, dried at 60°C for 8 hours, and calcined at 500°C for 4 hours to obtain solid a;
[0080] (7) Using a 0.1 mol / L ammonium chloride solution, solid a was subjected to ion exchange at a solid-liquid mass ratio of 1:10, and then calcined at 500℃ for 4 hours to obtain solid b;
[0081] (8) Using solid b as the active component of the catalyst, add 600g of kaolin, 130g of alumina sol, 400g of molecular sieve and 130g of silica sol in sequence, mix and stir to form a slurry, ball mill the slurry and then spray dry it in a spray dryer.
[0082] (9) The prepared microspheres were calcined at 500℃ for 2 hours to obtain the catalyst.
[0083] Example 2
[0084] (1) Place the waste eggshells in a ball mill and grind for 40 minutes to obtain eggshell powder;
[0085] (2) Add 3 mol sodium aluminate and 5 mol sodium hydroxide to 600 mol water and stir until homogeneous to obtain solution A;
[0086] (3) Mix 133 mol of 30% silica sol and 5 mol of urea evenly to obtain solution B;
[0087] (4) Pour solution B into solution A, add 1 wt% of eggshell powder (total mass of sodium aluminate and sodium hydroxide), and stir at room temperature (around 25°C) to obtain gel C;
[0088] (5) Transfer gel C to a reaction vessel and crystallize it at 170°C for 24 hours;
[0089] (6) The crystallized molecular sieve was washed with deionized water until neutral, dried at 60°C for 8 hours, and calcined at 500°C for 4 hours to obtain solid a;
[0090] (7) Using a 0.1 mol / L ammonium chloride solution, solid a was subjected to ion exchange at a solid-liquid mass ratio of 1:10, and then calcined at 500℃ for 4 hours to obtain solid b;
[0091] (8) Using solid b (i.e., modified molecular sieve) as the active component of the catalyst, add 600g of kaolin, 130g of alumina sol, 400g of molecular sieve and 130g of silica sol in sequence, mix and stir to form a slurry, ball mill the slurry and spray it in a spray dryer.
[0092] (9) The prepared microspheres were calcined at 500℃ for 2 hours to obtain the catalyst.
[0093] Example 3
[0094] (1) Place the waste eggshells in a ball mill and grind for 60 minutes to obtain eggshell powder;
[0095] (2) Add 3 mol sodium aluminate and 5 mol sodium hydroxide to 600 mol water and stir until homogeneous to obtain solution A;
[0096] (3) Mix 133 mol of 30% silica sol and 5 mol of urea evenly to obtain solution B;
[0097] (4) Pour solution B into solution A, add 1 wt% of eggshell powder (total mass of sodium aluminate and sodium hydroxide), and stir at room temperature (around 25°C) to obtain gel C;
[0098] (5) Transfer gel C to a reaction vessel and crystallize it at 170°C for 24 hours;
[0099] (6) The crystallized molecular sieve was washed with deionized water until neutral, dried at 60°C for 8 hours, and calcined at 500°C for 4 hours to obtain solid a;
[0100] (7) Using a 0.1 mol / L ammonium chloride solution, solid a was subjected to ion exchange at a solid-liquid mass ratio of 1:10, and then calcined at 500℃ for 4 hours to obtain solid b;
[0101] (8) Using solid b as the active component of the catalyst, add 600g of kaolin, 130g of alumina sol, 400g of molecular sieve and 130g of silica sol in sequence, mix and stir to form a slurry, ball mill the slurry and then spray dry it in a spray dryer.
[0102] (9) The prepared microspheres were calcined at 500℃ for 2 hours to obtain the catalyst.
[0103] Example 4
[0104] (1) Place the waste eggshells in a ball mill and grind for 80 minutes to obtain eggshell powder;
[0105] (2) Add 3 mol sodium aluminate and 5 mol sodium hydroxide to 600 mol water and stir until homogeneous to obtain solution A;
[0106] (3) Mix 133 mol of 30% silica sol and 5 mol of urea evenly to obtain solution B;
[0107] (4) Pour solution B into solution A, add 1 wt% of eggshell powder (total mass of sodium aluminate and sodium hydroxide), and stir at room temperature (around 25°C) to obtain gel C;
[0108] (5) Transfer gel C to a reaction vessel and crystallize it at 170°C for 24 hours;
[0109] (6) The crystallized molecular sieve was washed with deionized water until neutral, dried at 60°C for 8 hours, and calcined at 500°C for 4 hours to obtain solid a;
[0110] (7) Using a 0.1 mol / L ammonium chloride solution, solid a was subjected to ion exchange at a solid-liquid mass ratio of 1:10, and then calcined at 500℃ for 4 hours to obtain solid b;
[0111] (8) Using solid b (i.e., modified molecular sieve) as the active component of the catalyst, add 600g of kaolin, 130g of alumina sol, 400g of molecular sieve and 130g of silica sol in sequence, mix and stir to form a slurry, ball mill the slurry and spray it in a spray dryer.
[0112] (9) The prepared microspheres were calcined at 500℃ for 2 hours to obtain the catalyst.
[0113] Example 5
[0114] (1) Place the waste eggshells in a ball mill and grind for 120 minutes to obtain eggshell powder;
[0115] (2) Add 3 mol sodium aluminate and 5 mol sodium hydroxide to 600 mol water and stir until homogeneous to obtain solution A;
[0116] (3) Mix 133 mol of 30% silica sol and 5 mol of urea evenly to obtain solution B;
[0117] (4) Pour solution B into solution A, add 1 wt% of eggshell powder (total mass of sodium aluminate and sodium hydroxide), and stir at room temperature (around 25°C) to obtain gel C;
[0118] (5) Transfer gel C to a reaction vessel and crystallize it at 170°C for 24 hours;
[0119] (6) The crystallized molecular sieve was washed with deionized water until neutral, dried at 60°C for 8 hours, and calcined at 500°C for 4 hours to obtain solid a;
[0120] (7) Using a 0.1 mol / L ammonium chloride solution, solid a was subjected to ion exchange at a solid-liquid mass ratio of 1:10, and then calcined at 500℃ for 4 hours to obtain solid b;
[0121] (8) Using solid b (i.e., modified molecular sieve) as the active component of the catalyst, add 600g of kaolin, 130g of alumina sol, 400g of molecular sieve and 130g of silica sol in sequence, mix and stir to form a slurry, ball mill the slurry and spray it in a spray dryer.
[0122] (9) The prepared microspheres were calcined at 500℃ for 2 hours to obtain the catalyst.
[0123] Example 6
[0124] (1) Place the waste eggshells in a ball mill and grind for 60 minutes to obtain eggshell powder;
[0125] (2) Add 3 mol sodium aluminate and 5 mol sodium hydroxide to 600 mol water and stir until homogeneous to obtain solution A;
[0126] (3) Mix 133 mol of 30% silica sol and 5 mol of urea evenly to obtain solution B;
[0127] (4) Pour solution B into solution A, add 3 wt% of eggshell powder (total mass of sodium aluminate and sodium hydroxide), and stir at room temperature (around 25°C) to obtain gel C;
[0128] (5) Transfer gel C to a reaction vessel and crystallize it at 170°C for 24 hours;
[0129] (6) The crystallized molecular sieve was washed with deionized water until neutral, dried at 60°C for 8 hours, and calcined at 500°C for 4 hours to obtain solid a;
[0130] (7) Using a 0.1 mol / L ammonium chloride solution, solid a was subjected to ion exchange at a solid-liquid mass ratio of 1:10, and then calcined at 500℃ for 4 hours to obtain solid b;
[0131] (8) Using solid b (i.e., modified molecular sieve) as the active component of the catalyst, add 600g of kaolin, 130g of alumina sol, 400g of molecular sieve and 130g of silica sol in sequence, mix and stir to form a slurry, ball mill the slurry and spray it in a spray dryer.
[0132] (9) The prepared microspheres were calcined at 500℃ for 2 hours to obtain the catalyst.
[0133] Example 7
[0134] (1) Place the waste eggshells in a ball mill and grind for 60 minutes to obtain eggshell powder;
[0135] (2) Add 3 mol sodium aluminate and 5 mol sodium hydroxide to 600 mol water and stir until homogeneous to obtain solution A;
[0136] (3) Mix 133 mol of 30% silica sol and 5 mol of urea evenly to obtain solution B;
[0137] (4) Pour solution B into solution A, add 5 wt% of eggshell powder (total mass of sodium aluminate and sodium hydroxide), and stir at room temperature (around 25°C) to obtain gel C;
[0138] (5) Transfer gel C to a reaction vessel and crystallize it at 170°C for 24 hours;
[0139] (6) The crystallized molecular sieve was washed with deionized water until neutral, dried at 60°C for 8 hours, and calcined at 500°C for 4 hours to obtain solid a;
[0140] (7) Using a 0.1 mol / L ammonium chloride solution, solid a was subjected to ion exchange at a solid-liquid mass ratio of 1:10, and then calcined at 500℃ for 4 hours to obtain solid b;
[0141] (8) Using solid b (i.e., modified molecular sieve) as the active component of the catalyst, add 600g of kaolin, 130g of alumina sol, 400g of molecular sieve and 130g of silica sol in sequence, mix and stir to form a slurry, ball mill the slurry and spray it in a spray dryer.
[0142] (9) The prepared microspheres were calcined at 500℃ for 2 hours to obtain the catalyst.
[0143] Example 8
[0144] (1) Place the waste eggshells in a ball mill and grind for 20 minutes to obtain eggshell powder;
[0145] (2) Add 3 mol aluminum sulfate and 5 mol potassium hydroxide to 693.1 mol water and stir until homogeneous to obtain solution A;
[0146] (3) Mix 39.9 mol silica gel and 5 mol urea evenly to obtain solution B;
[0147] (4) Pour solution B into solution A, add 1 wt% of eggshell powder (total mass of aluminum sulfate and potassium hydroxide), and stir at room temperature (around 25°C) to obtain gel C;
[0148] (5) Transfer gel C to a reaction vessel and crystallize it at 150°C for 72 hours;
[0149] (6) The crystallized molecular sieve was washed with deionized water until neutral, dried at 50°C for 8 hours, and calcined at 600°C for 8 hours to obtain solid a;
[0150] (7) Using a 0.1 mol / L ammonium acetate solution, solid a was subjected to ion exchange at a solid-liquid mass ratio of 1:10, and then calcined at 600℃ for 8 hours to obtain solid b;
[0151] (8) Using solid b (i.e., modified molecular sieve) as the active component of the catalyst, add 600g of kaolin, 260g of acidified pseudoboehmite and 400g of molecular sieve in sequence, mix and stir to form a slurry, ball mill the slurry and then spray dry it in a spray dryer.
[0152] (9) The prepared microspheres were calcined at 500℃ for 2 hours to obtain the catalyst.
[0153] Example 9
[0154] (1) Place the waste eggshells in a ball mill and grind for 20 minutes to obtain eggshell powder;
[0155] (2) Add 3 mol aluminum hydroxide and 20 mol tetrapropylammonium hydroxide to 678.1 mol water and stir until homogeneous to obtain solution A;
[0156] (3) Mix 40.3 mol of tetraethyl orthosilicate (99%) and 5 mol of ammonium fluoride evenly to obtain solution B;
[0157] (4) Pour solution B into solution A, add 1 wt% of eggshell powder (total mass of aluminum hydroxide and tetrapropylammonium hydroxide), and stir at room temperature (around 25°C) to obtain gel C;
[0158] (5) Transfer gel C to a reaction vessel and crystallize it at 180°C for 24 hours;
[0159] (6) The crystallized molecular sieve was washed with deionized water until neutral, dried at 40°C for 15 h, and calcined at 500°C for 6 h to obtain solid a;
[0160] (7) Using a 0.1 mol / L ammonium nitrate solution, solid a was subjected to ion exchange at a solid-liquid mass ratio of 1:10, and then calcined at 600℃ for 8 hours to obtain solid b;
[0161] (8) Using solid b (i.e., modified molecular sieve) as the active component of the catalyst, add 600g of kaolin, 260g of water glass and 400g of molecular sieve in sequence and mix them into a slurry. After ball milling the slurry, spray it in a spray dryer.
[0162] (9) The prepared microspheres were calcined at 500℃ for 2 hours to obtain the catalyst.
[0163] Performance testing
[0164] 1. X-ray fluorescence spectroscopy test
[0165] Test results are as follows Figure 1 As shown in Table 1:
[0166] Table 1
[0167] Comparative Example 1 94.11 5.31 0 Example 1 94.23 5.36 0.81 Example 2 94.35 5.35 0.8 Example 3 94.25 5.33 0.82 Example 4 94.52 5.40 0.75 Example 4 94.13 5.31 0.72 Example 6 94.28 5.34 2.1 Example 7 94.41 5.38 3.5
[0168] Depend on Figure 1 The XRD patterns show that the modified molecular sieves obtained in Examples 1-7 and the molecular sieve obtained in Comparative Example 1 all exhibit MFI characteristic diffraction peaks, and no diffraction peaks of other phases were observed. Therefore, the synthesized molecular sieve can be identified as ZSM-5 molecular sieve. No diffraction peaks of calcium oxide were observed in the XRD patterns. This may be due to the low amount of calcium introduced or the small size of the introduced calcium particles, making them unobservable in the XRD.
[0169] 2. Surface area and pore volume test
[0170] The test results are shown in Table 2:
[0171] Table 2
[0172]
[0173] Table 1 shows that the molecular sieve synthesized without eggshell powder, i.e., Comparative Example 1, does not contain calcium. In Examples 1-5, eggshell powder milled for 20 min, 40 min, 60 min, 80 min, and 120 min respectively was used as an additive, with an addition content of 1 wt%. Elemental analysis results show that although the milling time differed, the calcium content in the five synthesized molecular sieves was essentially the same due to the identical amount of eggshell powder added. Furthermore, it can be seen that the calcium content in Examples 4 and 5 decreased slightly due to the longer milling time. This may be because the milling process ground the eggshell powder too finely, resulting in some powder not remaining inside the molecular sieve. This is also verified by the pore analysis in Table 2. In Examples 1-5, the mesopore specific surface area of the eggshell powder-guided molecular sieve increased with increasing milling time. When the milling time was further extended to 80 min and 120 min, the amount of mesopores introduced decreased.
[0174] Comparing Examples 3, 6, and 7, all three used eggshell powder ball-milled for 60 minutes, but the addition amounts were 1 wt%, 3 wt%, and 5 wt%, respectively. With increasing eggshell powder content, the amount of calcium detected in the molecular sieve significantly increased, but it was also clear that the increase was not proportional to the amount introduced. This means that excessive eggshell powder cannot fully function as a mesoporous structure guiding agent and calcium source. In pore analysis, the mesoporous specific surface area also increased with increasing eggshell powder content; however, in Examples 6 and 7, the difference was not significant, which can be attributed to the excessive introduction of eggshell powder, resulting in no further mesoporous formation.
[0175] 3. SEM characterization
[0176] The modified molecular sieves or molecular sieves (i.e., solid b) obtained in Examples 1-7 and Comparative Example 1 were characterized by SEM, and the results are as follows: Figure 2 As shown, it can be seen that Comparative Example 1, which is the molecular sieve sample without added eggshell powder, exhibits a blocky morphology, while in Examples 1-7, the molecular sieves clearly show an aggregated state of small particles with clearly visible mesopores.
[0177] 4. Catalytic evaluation and testing of fixed fluidized bed reactors
[0178] The testing method is as follows:
[0179] Prepare 200g of catalyst and add it to the fixed fluidized bed reactor. Set the system temperature to 630℃, nitrogen flow rate to 200mL / min, and water flow rate to 6g / min. After gasification and heating with nitrogen, reflux the oil pump for 1min, add 20g of oil, react for 8min, strip for 20min, then heat to 750℃ and regenerate for 120min. Regeneration is then complete.
[0180] After the reaction is complete, record the influent water, oil, and gas flow rates. Analyze the refinery gas and collect the liquid product.
[0181] The physical properties of the feedstock are shown in Table 3 below:
[0182] Table 3
[0183]
[0184]
[0185] The test results are shown in Table 4 below:
[0186] Table 4
[0187]
[0188] As shown in Table 4, in Examples 1-3, the longer the ball milling time of eggshell powder, the higher the conversion rate of the light hydrocarbon cracking reaction, accompanied by a higher diene yield and lower coke yield. However, with further extension of the ball milling time, a decrease occurred in Examples 4 and 5, which may be related to the decrease in the surface area of the mesopores in the pore structure. In Examples 3, 6, and 7, as the amount of eggshell powder introduced increased, the conversion rate gradually increased, the diene yield also increased significantly, and the coke yield decreased. This is directly proportional to the amount of calcium and mesopores introduced. The above results indicate that the light hydrocarbon cracking catalyst prepared using eggshell powder has high conversion rate, good selectivity, and strong anti-coking ability, making it suitable for the field of light hydrocarbon cracking with high diene production.
[0189] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A modified molecular sieve, characterized in that, It includes aluminosilicate molecular sieves and calcium oxide present in the aluminosilicate molecular sieves; the calcium oxide is uniformly distributed in the channels of the aluminosilicate molecular sieves to reduce the density of acidic sites in the aluminosilicate molecular sieves. The silica-aluminum molecular sieve has a composite pore structure of micropores and mesopores. The ratio of the total mass of the silica-alumina molecular sieve to the mass of calcium oxide is (40~250):1; The modified molecular sieve is prepared by a method comprising the following steps: The silicon source, aluminum source and calcium source are mixed under alkaline conditions, crystallized and calcined to obtain an intermediate; The intermediate was ion-exchanged with an ammonium salt and then calcined to obtain a modified molecular sieve. The calcium source is encapsulated inside the molecular sieve during the process of growing crystals from the molecular sieve. After calcination, it forms mesopores, and the introduced calcium remains inside the mesopores to form calcium oxide.
2. The modified molecular sieve according to claim 1, characterized in that, The silica-alumina molecular sieve is any one or more of ZSM-5 molecular sieve, Y-type molecular sieve, ZSM-35 molecular sieve, or β molecular sieve.
3. The modified molecular sieve according to claim 1 or 2, characterized in that, The calcium oxide is derived from calcium carbonate.
4. The modified molecular sieve according to claim 3, characterized in that, The calcium carbonate is sourced from waste eggshells.
5. A method for preparing a modified molecular sieve as described in any one of claims 1 to 4, characterized in that, include: The silicon source, aluminum source and calcium source are mixed under alkaline conditions, crystallized and calcined to obtain an intermediate; The intermediate was subjected to ion exchange with an ammonium salt, and the modified molecular sieve was obtained after calcination.
6. The preparation method according to claim 5, characterized in that, The silicon source is selected from any one or more of silica sol, tetraethyl orthosilicate, or silica gel. The aluminum source is selected from any one or more of sodium aluminate, aluminum hydroxide, aluminum sulfate, or boehmite. The calcium source is selected from calcium carbonate; The ammonium salt is selected from any one or more of ammonium chloride, ammonium nitrate, or ammonium acetate.
7. A catalyst, characterized in that, Includes carrier, binder, and active ingredient; The active component is the modified molecular sieve according to any one of claims 1 to 4 or the modified molecular sieve prepared according to the preparation method according to claim 5 or 6.
8. The catalyst according to claim 7, characterized in that, The carrier is selected from kaolin; The binder is selected from any one or more of alumina sol, silica sol, acidified boehmite, water glass, or aluminum phosphate.
9. The catalyst according to claim 7 or 8, characterized in that, The catalyst, by weight, comprises 20-40 parts of support, 10-30 parts of binder, and 30-50 parts of active component.
10. The application of the modified molecular sieve according to any one of claims 1 to 4, the modified molecular sieve prepared by the preparation method according to claim 5 or 6, or the catalyst according to any one of claims 7 to 9 in the cracking of light hydrocarbons.
Citation Information
Patent Citations
Preparation method and application of Mn-Zn-P composite modified molecular sieve
CN117160528A
Iron-containing ZSM-5 molecular sieve as well as preparation method and application thereof
CN117430126A
Preparation method of MFI molecular sieve of microporous-mesoporous structure
CN107640776A